Emerging roles of microRNAs in septic cardiomyopathy - Wu, Mingyan; Li, Guangdong; Wang, Wenjun; Ren, Hongsheng (Frontiers in Pharmacology, 2023)
As one of the serious complications of sepsis, septic cardiomyopathy has gained more and more attention, because of its high morbidity and mortality. With the in-depth study of septic cardiomyopathy, several methods have been adopted clinically but have poor therapeutic effects due to failure to find precise therapeutic targets. In recent years, microRNAs have been found to be related to the pathogenesis, diagnosis, and treatment of septic cardiomyopathy via regulating immunity and programmed cell death. This paper reviews the role of microRNAs in septic cardiomyopathy, aiming to provide new targets for the diagnosis and treatment of septic cardiomyopathy.